Optimisation of the synthesis of ZrC coatings in a radio frequency induction-heating chemical vapour deposition system using response surface methodology - Biira, S.; Crouse, P. L.; Bissett, H.; Alawada, B. A. B; Hlatshwayo, T. T.; Nel, J. T.; Malherbe, J. B. (Thin Solid Films, 2017)
A chemical vapour deposition process using radio frequency induction heating operating at atmospheric pressure was developed for the deposition of ZrC coatings. The precursors utilised in this process were zirconium tetrachloride and methane as zirconium and carbon sources respectively, in an excess of hydrogen. Additionally, a stream of argon was used to, first, remove oxygen from the reactor and then to sweep the vapourised ZrCl4 at 300 °C to the reaction chamber. The ZrC coatings were deposited on graphite substrates at substrate temperatures in the range of 1200 °C–1600 °C. The molar ratio of CH4/ZrCl4 was varied from 6.04 to 24.44. Before the start of the deposition process, thermodynamic feasibility analysis for the growth of ZrC at atmospheric pressure was also carried out. Response surface methodology was applied to optimise the process parameters for the deposition of ZrC coatings. A central composite design was used to investigate the effects of temperature and molar ratio of CH4/ZrCl4 on the growth rate, atomic ratio of C/Zr and crystallite size of ZrC coatings. Quadratic statistical models for growth rate and crystallite size were established. The atomic ratio of C/Zr followed a linear trend. It was found that an increase in substrate temperature and CH4/ZrCl4 ratio resulted in increased growth rate of ZrC coatings. The carbon content (and concomitantly the atomic ratio of C/Zr) in the deposited coatings increased with temperature and molar ratio of CH4/ZrCl4. The substrate temperature of 1353.3 °C and the CH4/ZrCl4 molar ratio of 10.41were determined as the optimal condition for growing near-stoichiometry ZrC coatings. The values were 1.03, 6.05 μm/h and 29.8 nm for C/Zr atomic percentage ratio, growth rate and average crystallite size respectively
Keywords: Zirconium carbide; Chemical vapour deposition; Substrate temperature; Methane; Zirconium chloride; Response surface model; Growth rate; Crystallite size; Energy-dispersive X-ray spectroscopy